Modelling the development of affective and cognitive processes in computer programming and their interrelationships - Mooi, Lee Choo. (2009)
In order to promote liking and ameliorate computer programming anxiety, teachers need to understand the cognitive processes underlying these affective traits and the affective processes underlying computer programming competence. Interest in this interplay of affect and cognition led to the proposition of models to explain (i) problem-solving processes; (ii) inter-relationships among liking for, anxiety and competence in computer programming; and (iii) computer programming understanding. To validate these models, cognitive and affective responses were collected from Grade 11 Computing students via three assessment instruments: Computer Programming Algorithm Test, Computer Programming Anxiety Scale, and Liking for Computer-related Activities Scale; and analysed using systemic networks, IRT and Dual Scaling techniques.